PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2016) - Tuffahati Dhiagriya Kuspinta; Achmad Husaini (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This study is aimed to investigate the effect of intellectual capital towards manufacturing companies profitability listed in Indonesia Stock Exchange for the last three years observation in 2014, 2015, 2016.Furthermore, explanatory was used as the kind of study. Meanwhile, the population of this study used Manufacturing Companies listed in Indonesia Stock Exchange (BEI) in the time period of 2014-2016 with amount of 150 companies.There were two types of variable in this study. The independent variable was intellectual capital with the proxy (VACA, VAHU, STVA). The dependent variable was profitability with proxy (ROA) Multiple linear regression was used as the analysis method.The result of the study showed that; 1) the effect of intellectual capital proxy with Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA), simultaneously has a significant positive effect on the profitability of the company that proxied with Return On Assets (ROA); 2) the study found that Value Added Capital Employed (VACA) was dominantly effected on the profitability of the company. Kеywords:Intellectual Capital, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Return On Assets (ROA) АBSTRАK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh intellectual capital terhadap profitabilitas perusahaan manufaktur yang terdaftar di bursa efek Indonesia selama tiga tahun pengamatan, yakni tahun 2014,2015,dan 2016.Jenis penelitian yang digunakan adalah penelitian explanatory. Populasi penelitian adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) pada periode tahun 2014-2016 yang berjumlah 150 perusahaan. Penelitian ini menggunakan dua tipe variabel terdiri dari variabel independen yaitu intellectual capital diproksikan dengan (VACA,VAHU,STVA) dan variabel dependen profitabilitas diproksikan dengan (ROA). Metode analisis yang digunakan dalam penelitian ini adalah regresi linier berganda.Hasil dari penelitian ini yaitu; 1) Pengaruh intellectual capital yang diproksikan dengan Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), dan Structural Capital Value Added (STVA),secara simultan mempunyai pengaruh yang signifikan positif terhadap profitabilitas perusahaan yang diproksikan dengan Return On Assets (ROA); 2) penelitian ini menemukan bahwa Value Added Capital Employed (VACA) berpengaruh paling dominan terhadap profitabilitas perusahaan. Kаtа Kunci:Intellectual Capital, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Return On Assets (ROA)